Unacceptable failure rate of a ceramic-coated posterior cruciate-substituting total knee arthroplasty - David Lionberger, MD (Arthroplasty Today, 2019)
Background: Aseptic loosening is one of the most elusive problems in total knee arthroplasty. We compared the failure rates of posterior cruciate-substituting total knee arthroplasty utilizing implants with hardened surface coating to a previous cohort of patients who underwent the procedure with traditional cruciate-retaining noncoated cobalt-chrome implants. Methods: A retrospective study was conducted of 1099 total knee arthroplasties performed from 2009 to 2017. Two hundred forty-nine total knee arthroplasties performed from January 2015 to March 2017 under a single design were reviewed retrospectively and compared to the author’s previous 850 total knee arthroplasties performed from January 2009 to December 2014 under a different design. Results: This series demonstrated an alarming debonding of cement in the tibial implant. The resultant failure rate of 6% (P < .001) is higher than observed in 850 total knee arthroplasties in the previous 5 years and higher than those reported in the literature giving cause for concern regarding this implant. Conclusions: Due to the observed excessive failure rate, the authors recommend exercising high levels of caution using this implant with hardened surface treatment until further testing can be ascertained as to the root cause of failure. Keywords: Cement adhesion, Coated implant surface, Failure, Loosening, Total knee arthroplasty